2021
DOI: 10.1177/10298649211030318
|View full text |Cite
|
Sign up to set email alerts
|

Listening to music to cope with everyday stressors

Abstract: Everyday stressors—the irritating and disturbing events that happen in the context of everyday life—are common. The present research examined the relationship between everyday stressors and the use of music listening as a coping mechanism. In particular, it examined the use of music listening to cope with different types of everyday stressor and examined the relationship between this usage and listener characteristics, including demographics and music engagement style. Participants in the USA, Australia, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…Moreover, people with a more strongly affective style of music engagement were more likely to report evocative and expressive and sad emotional experiences. This aligns with previous findings that emotion regulation is the primary reason for listening to music (Schäfer et al, 2013) and that an affective style is positively associated with listening to music to cope with everyday stressors (Krause et al, 2023). The affective style of music engagement is also characterized by “emotional processes involved with cathartic and expressive engagement” (Greenberg & Rentfrow, 2015, n.p.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, people with a more strongly affective style of music engagement were more likely to report evocative and expressive and sad emotional experiences. This aligns with previous findings that emotion regulation is the primary reason for listening to music (Schäfer et al, 2013) and that an affective style is positively associated with listening to music to cope with everyday stressors (Krause et al, 2023). The affective style of music engagement is also characterized by “emotional processes involved with cathartic and expressive engagement” (Greenberg & Rentfrow, 2015, n.p.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, a growing body of research has evidenced the role of music and music listening in promoting health and well-being (Krause et al, 2018(Krause et al, , 2021McCrary et al, 2022;Raglio, 2021;Vidas et al, 2022), including both explicitly therapeutic and everyday engagement. Benefits arise, for example, through the association of listening with relaxation and enjoyment (e.g., Baylan et al, 2018;Diaz, 2013) and its use as a coping mechanism for dealing with stress (Adiasto et al, 2022;Krause et al, 2023;Vidas et al, 2021), pain (Howlin et al, 2022), and anxiety (Harney et al, 2023). Research has supported the use of everyday listening practices to cope with stress (e.g., Krause et al, 2023) manage one's moods and emotions (Randall et al, 2014;Saarikallio et al, 2013), and help with self-awareness (e.g., Elvers et al, 2018;Schäfer et al, 2013), although the extent to which music listening is effective (e.g., on reducing stress) depends on the individual (Galanakis et al, 2009) and their listening style (e.g., Miranda & Claes, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This pertains to the outcomes of various studies examining the effects of listening to music as ambient sound. In recent research conducted by Krause et al, participants reported listening to music for emotional support and disengagement from problems [64]. Additionally, the same research group suggests that during the COVID-19 lockdown, listening to music was correlated with increased life satisfaction [9].…”
Section: Features Selection and Features Importancementioning
confidence: 94%